Inhomogeneous reduction and its relation to grain growth of titania during flash sintering. (October 2018) - Charalambous, Harry; Jha, Shikhar Krishn; Wang, Han; Phuah, Xin Li; Wang, Haiyan; Tsakalakos, Thomas
Abstract: Flash sintering under DC electric field partially reduces titania (rutile) and promotes abnormal grain growth near the anode. The resulting reduction in grain boundary density reduces the number of vacancy traps and enhances the O 2− ion conductivity through the specimen, facilitating greater non-stoichiometry. The observed gradient of densification and grain-growth across the two ends has been linked to the Peltier effect which causes heating at the anode-electrode junction and cooling at the cathode-electrode junction. Graphical abstract: Unlabelled Image